2011
DOI: 10.5194/hess-15-547-2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of catchment contributing areas and storm runoff in flat terrain subject to urbanisation

Abstract: Abstract. Contributing Catchment Area Analysis (CCAA) is a spatial analysis technique developed and used for estimation of the hydrological connectivity of relatively flat catchments. It allows accounting for the effect of relief depressions on the catchment rainfall-runoff relationship which is not commonly considered in hydrological modelling. Analysis of distributed runoff was based on USDA runoff curves numbers (USDA, 1986), which utilised the spatial information on land cover and soil types, while CCAA wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Connected impervious surfaces, artificial slopes and channel networks in urban areas, coupled with urban-induced high-intensity storms, imply that surface runoff is dominated by infiltration excess or Hortonian overland flow (Johnson et al 2003;Barron et al 2011). These changes in catchment properties and runoff coefficients may have profound effects on on-site and downstream hydrographs (Fig.…”
Section: Rainfall-runoff Relationshipsmentioning
confidence: 97%
“…Connected impervious surfaces, artificial slopes and channel networks in urban areas, coupled with urban-induced high-intensity storms, imply that surface runoff is dominated by infiltration excess or Hortonian overland flow (Johnson et al 2003;Barron et al 2011). These changes in catchment properties and runoff coefficients may have profound effects on on-site and downstream hydrographs (Fig.…”
Section: Rainfall-runoff Relationshipsmentioning
confidence: 97%
“…A study undertaken by Barron et al (2011) found that urbanisation and the consequent drainage system upgrades were responsible for a 30-100 % increase in the predicted runoff volume. Similarly, Chen et al (2014) noted that because of rapid urbanisation, the mean annual runoff from middle and lower Yangzi River catchments in China increased by 16 and 15 %, respectively, over the period of 1955-2011.…”
Section: Runoff Volumementioning
confidence: 99%
“…As a lowland watershed, no steep slopes exist and the elevation varies from 95 m to 110 m above sea level. Thus, the topography of the watershed does not have a major influence on the surface runoff, which instead is dominated by the land use type (Barron et al, 2011). Urban areas cover 58.7 % of the catchment and the percentage of impervious areas in the whole catchment is 32 %.…”
Section: Test Catchmentmentioning
confidence: 99%
“…Urbanization and the resulting land-use change strongly affect the water cycle in watersheds (Rosso and Rulli, 2002;Ott and Uhlenbrook, 2004;Shepherd, 2005;Brath et al, 2006;Clarke, 2007;Quilbé et al, 2008;Barron et al, 2011;Jung et al, 2011;Schaefli et al, 2011). By 2020 it is estimated that more than 80 % of European citizens will be living in urban agglomerations and there is no apparent slowing in this trend (EEA, 2006).…”
Section: Introductionmentioning
confidence: 99%